Pengaruh Perbandingan Video E-Learning dalam meningkatkan Kognitif Psikomotor terhadap Asuhan Keperawatan Jiwa pada Klien Resiko Perilaku Kekerasan Bagi Mahasiswa Keperawatan - Nur Sriyanti; Novita Ranti Muntiari; Rosaleni Rejin (Postgraduate, University of Mataram, 2025)
This study aimed to analyze the comparative effectiveness of e-learning videos created by course lecturers versus externally produced videos in enhancing nursing students' cognitive and psychomotor skills regarding psychiatric nursing care for clients at risk of violent behavior. A quasi-experimental design with a pretest-posttest approach was employed. Student cohorts were divided into an intervention group, which used lecturer-made videos, and a control group, which used externally made videos. The findings revealed a substantial improvement in the intervention group, with cognitive skills increasing by 86.5% and psychomotor skills by 69.77%. In contrast, the control group showed no significant increase. This indicates that lecturer-created videos, likely due to their tailored relevance to the specific curriculum and learning context, are a more potent educational tool. It is concluded that e-learning videos developed by the course lecturers are significantly more effective than external videos in improving both the knowledge and practical skills of nursing students. The use of curated, internally developed video media is therefore highly recommended for optimizing learning outcomes in specialized nursing education.